Effect of Rake Angle on Stress, Strain and Temperature on the Edge of Carbide Cutting Tool in Orthogonal Cutting Using FEM Simulation - Hendri Yanda; Jaharah A. Ghani; Che Hassan Che Haron (Institute for Research and Community Services, Institut Teknologi Bandung, 2010)
Demand for higher productivity and good quality for machining parts has encourage many researchers to study the effects of machining parameters using FEM simulation using either two or three dimensions version. These are due to advantages such as software package and computational times are required. Experimental work is very costly, time consuming and labor intensive. The present work aims to simulate a three-dimensional orthogonal cutting operations using FEM software (deform-3D) to study the effects of rake angle on the cutting force, effective stress, strain and temperature on the edge of carbide cutting tool. There were seven runs of simulations. All simulations were performed for various rake angles of -15 deg, -10 deg, -5 deg, 0 deg, +5 deg, +10 deg, and +15 deg. The cutting speed, feed rate and depth of cut (DOC) were kept constant at 100 m/min, 0.35 mm/rev and 0.3 mm respectively. The work piece used was ductile cast iron FCD500 grade and the cutting tool was DNMA432 series (tungsten, uncoated carbide tool, SCEA = 0; and radius angle 55 deg). The analysis of results show that, the increase in the rake angle from negative to positive angle, causing the decrease in cutting force, effective stress and total Von Misses strain. The minimum of the cutting force, effective stress and total Von Misses strain were obtained at rake angle of +15 deg. Increasing the rake caused higher temperature generated on the edge of carbide cutting tool and resulted in bigger contact area between the clearance face and the workpiece, consequently caused more friction and wear. The biggest deformation was occurred in the primary deformation zone, followed by the secondary deformation zone. The highest stress was also occurred in the primary deformation zone. But the highest temperature on the chip usually occurs in secondary deformation zone, especially in the sliding region, because the heat that was generated in the sticking region increased as the workpiece was adhered by the tool and later it was sheared in high frictional force.